2003
DOI: 10.1046/j.1440-0960.2003.00005.x
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of dermatophyte infection in Auckland, New Zealand

Abstract: This report describes the epidemiology of culture-proven dermatophyte infection in Auckland, New Zealand. The authors undertook a retrospective review of laboratory data for the period from June 1999 to July 2002. There were 10 004 dermatophyte isolates. The most common isolates were Trichophyton rubrum (69%) and Trichophyton mentagrophytes (19%). Microsporum canis was mainly isolated from children. The prevalence of T. mentagrophytes increased with patient age (P < 0.001). Trichophyton rubrum was most common … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
13
1
1

Year Published

2005
2005
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 12 publications
3
13
1
1
Order By: Relevance
“…Indeed, an increase in infection with increasing age is well established (28,43,53,96,98,107). This observation is consistent with the view that changes in the immune response which occur with advancing age lead to disease susceptibility.…”
Section: Dermatophytosis: An Increasing Problemsupporting
confidence: 84%
“…Indeed, an increase in infection with increasing age is well established (28,43,53,96,98,107). This observation is consistent with the view that changes in the immune response which occur with advancing age lead to disease susceptibility.…”
Section: Dermatophytosis: An Increasing Problemsupporting
confidence: 84%
“…Microsporum canis was more common in children, while the prevalence of T. mentagrophytes was significantly associated with the age of the patients. Incidence of mycotic infections was 2.9/1000 population, as for other Western countries (Singh et al 2003). These results were also confirmed by another study on Greek children under 13, affected by dermatomycoses: in this population, the most frequently isolated fungus was Microsporum canis followed by Trichophyton rubrum and Candida albicans.…”
Section: Introductionsupporting
confidence: 82%
“…Contrary to a previous report, which found that the prevalence of T. mentagrophytes increases with age (15), we found that T. mentagrophytes infection was greatest among the middle-aged, which suggests that social interactions may be an important factor of T. mentagrophytes infection in Korea. Furthermore, the incidence rate in men was much higher than that in women.…”
Section: Discussioncontrasting
confidence: 99%